2014
DOI: 10.1149/2.0061411jss
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Chemical Vapor Deposition of Nickel Ferrite Thin Films Using Organometallic Precursor Combination

Abstract: This work introduces the fabrication of nano scale magnetostrictive NiFe2O4 (NFO) thin films using reduced pressure metallorganic chemical vapor deposition (MOCVD) with programmable cyclic pulsing of novel precursor combination — n-butylferrocene and nickelocene. Using a custom-designed CVD system, different rate-limiting steps and Ea in the CVD of iron oxide and nickel oxide depositions are discussed. Both cyclic-deposition and co-deposition modes were investigated through NFO depositions on silicon substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
(63 reference statements)
3
13
0
Order By: Relevance
“…For both reaction systems the film growth rate increases exponentially with substrate temperature according to the Arrhenius low at lower growth temperatures. The value of apparent activation energy for the temperature region 600-700 K was 80 ± 5 kJ·mol −1 in both cases and agrees well with [12,16,17] (60-90 kJ·mol −1 ). As the temperature increases, the growth rate becomes nearly independent on temperature.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…For both reaction systems the film growth rate increases exponentially with substrate temperature according to the Arrhenius low at lower growth temperatures. The value of apparent activation energy for the temperature region 600-700 K was 80 ± 5 kJ·mol −1 in both cases and agrees well with [12,16,17] (60-90 kJ·mol −1 ). As the temperature increases, the growth rate becomes nearly independent on temperature.…”
Section: Resultssupporting
confidence: 80%
“…Nickelocene and its derivatives are the most promising precursors for MOCVD of Ni-containing films [16,17]. Yeh et al reported that NiO layers have been deposited at 580 K from Ni(Cp) 2 (bis-cyclopentadienyl) Ni.…”
Section: Introductionmentioning
confidence: 99%
“…The observed peaks at 530.9 and 532.3 eV (upper panel, Figure c) were due to metal hydroxide (M−OH) bonds and O 2− incorporation in the subsurface of the film, respectively; which is common in transition metal oxides . After electrochemical activation a strong peak emerged at 529.7 eV, indicating a nickel ferrite lattice oxygen while the peak due to O 2− incorporation in the subsurface of the film decreased in intensity; however, the peak due to M−OH persisted. For the S 2p spectrum there was a broad feature with two peaks at 168 and 171 eV (Figure d) which was attributed to oxidised sulphur species such as sulfate and sulphite, respectively; which was not surprising for a natural iron ore sample.…”
Section: Resultsmentioning
confidence: 98%
“…The O 1s XPS spectra for the raw ore and activated ore are shown in Figure c. The observed peaks at 530.9 and 532.3 eV (upper panel, Figure c) were due to metal hydroxide (M−OH) bonds and O 2− incorporation in the subsurface of the film, respectively; which is common in transition metal oxides . After electrochemical activation a strong peak emerged at 529.7 eV, indicating a nickel ferrite lattice oxygen while the peak due to O 2− incorporation in the subsurface of the film decreased in intensity; however, the peak due to M−OH persisted.…”
Section: Resultsmentioning
confidence: 99%
“…The core scan of the sample containing nickel ferrite, both the Ni 2p 3/2 and Fe 2p 3/2 main peak centred at 855.2 eV and 711.2 eV respectively suggesting the structure of NiFe 2 O 4. The de‐convolution of the Ni 2p peak of composites shows four peaks (Figure ). The peaks centred at a binding energy of 855.2 and 873.4 eV correspond to Ni 2p 3/2 and Ni 2p 1/2 , respectively.…”
Section: Vacuum Trapping Of Nife2o4 Nanoparticles In Porous Pvdf Membmentioning
confidence: 99%